Determination of a mango (Mangifera indica Linn.) leather extender - Miguel, Maria Rosario S.
ABSTRACT The study on the determination of a mango leather extender consisted of 2 phases: the first was to determine the more suitable extender between cassava starch and agar; while thesecond was to determine the percentage of substitution of the extender chosen from phase I. Mango puree was prepared and divided into three samples. To one sample, 1% agar solution was added. To another, cassava starch was added. The third is for the control. These were dried and stored for 10 days. After 10 days, these samples were evaluated for color using the Munsell Color Chart and by spectrophotometer analysis, and also for the tensile strength. Results showed that the leather with 1% agar solution was the best product. It gave a desirable color at Hue 7/10. The absorbance reading is 0.071nm. It has a tensile strength of 21.29 gms/sq.cm. which gave a tough leather. This sample had a smooth and even surface. Three levels of substitution of agar solution were studied: 25%, 50% and 75% by weight of puree. After 10 days of storage, the samples were subjected to sensory evaluation, pigmentation and tensile strength. The results showed that a 25% level of substitution was most desirable. This product sample gave a firm and chewy texture with a tensile strength of 5.03 gms/ sq.cm. It has a distinct mango flavor and is generally most preferred among the three samples. It is recommended that further studies for a better color be studied for this product.